IMPLEMENTASI PELAKSANAAN HAK ASASI TERSANGKA TINDAK PIDANA PELANGGARAN PASAL 310 AYAT 4 UNDANG-UNDANG NO 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN (STUDI KASUS DI KEPOLISIAN RESOR KUANTAN SINGINGI) - Afrianti, Henny; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Human rights are the rights of every individual that must be protected and must be respected by everyone. In Indonesia, human rights are explicitly stated in the Post-Amendment 1945 Constitution. Likewise, the human rights of the perpetrators or suspects in criminal offenses in violation of Article 310 Paragraph (4) due to their negligence cause traffic accidents resulting in other deaths. In this case the referred human rights in the form of legal protection of perpetrators or suspects. Legal protection for victims of traffic accidents must be provided, as well as legal protection for offenders because of negligence is entitled to get the same protection. Because in these accidents often the mistakes are not entirely from traffic violators, negligence can be done by the victims themselves.The purpose of writing this thesis, namely: First, to find out whether fully carried out human rights against perpetrators of traffic violators or suspects because of negligence caused traffic accidents and caused others to die, Second, to find out the obstacles in implementing human rights against perpetrators of past violators cross or suspect. The research method used in this study is the type of sociological research, namely the interview method within the Kuantan Singingi Police Department.From the results of the study, based on two problem formulations can be concluded. First, the implementation of the human rights of a criminal offense in violation of Article 310 Paragraph (4) of Law Number 22 Year 2009 concerning Traffic and Road Transportation in the Kuantan Singingi Police Station in the form of legal protection for suspects is still not fully fulfilled, there are rights of the suspect which have not yet been achieved, among these rights are legal protection such as: the perpetrator is immediately secured at the nearest police station, detains the perpetrator, provides understanding / understanding to the perpetrator, makes arrests based on the rules stipulated in the Criminal Procedure Code . Second, the obstacles faced by the Kuantan Singingi District Police in carrying out the rights of suspects in traffic offenses namely the victim's family do not want to do an autopsy examination of the bodies of the accident victims, the perpetrators are difficult to question, ask the police not to proceed with the case to court, it is difficult looking for witnesses in the incident, There is a mutual agreement between the parties, the limited number of state lawyers in Kuantan Singingi Regency for suspects, cell rooms or detainees that are still lacking for suspects in traffic accident cases.Keywords: Implementation - HAM - Suspect - Traffic Accident